Effects of 5-Week of FIFA 11+ Warm-Up Program on Explosive Strength, Speed, and Perception of Physical Exertion in Elite Female Futsal Athletes - Antonino Patti; Valerio Giustino; Stefania Cataldi; Vito Stoppa; Federica Ferrando; Riccardo Marvulli; Giacomo Farì; Şahin Fatma Neşe; Antonino Bianco; Antonella Muscella; Gianpiero Greco; Francesco Fischetti (Sports, 2022)
Futsal is a sport that originates from soccer and is increasingly practiced all over the world. Since training and warm-up protocols should be sport-specific in order to reduce injuries and maximize performance, this study aimed to evaluate the effects of 5 weeks of the FIFA 11+ warm-up program on explosive strength, speed, and perception of physical exertion in elite female futsal athletes. Twenty-nine elite female futsal athletes participating in the Italian national championships were divided into two groups: the experimental group (EG) underwent 5 weeks of the FIFA 11+ warm-up program, and the control group (CG) underwent 5 weeks of a dynamic warm-up. We evaluated any effect on explosive strength (by Squat Jump test), speed (by Agility T-test), and perception of physical exertion (by Borg CR-10 scale). All measurements were carried out by a technician of the Italian Football Federation before (T0), at the middle (T1), and at the end (T2) of the protocol. The EG showed significant improvements on performances between T0 vs. T1 and T0 vs. T2 both in the Squat Jump test (p = 0.0057 and p = 0.0030, respectively) and in the Agility T-test (p = 0.0075 and p = 0.0122). No significant differences were found in the Squat Jump test performances in the CG, while significant improvements were detected in the Agility T-test performances (p = 0.0004 and p = 0.0053, T0 vs. T1 and T0 vs. T2, respectively). As for the Borg CR-10 scale, we found a significant difference between T0 and T2 in the EG (p = 0.017) and no differences in the CG. This study showed that 5 weeks of the FIFA 11+ warm-up program improves the jumping performance of female futsal athletes without adversely affecting speed. These findings can be useful for coaches and athletic trainers in order to consider FIFA 11+ warm-up program also in female futsal athletes.